Biofilm formation of periodontal pathogens on hydroxyapatite surfaces: Implications for periodontium damage - Norzawani, Jaffar; Toshiki, Miyazaki; Toshinari, Maeda (John Wiley and Sons Inc., 2016)
Biofilm formation of periodontal pathogens on teeth surfaces promotes the progression of periodontal disease. Hence, understanding the mechanisms of bacterial attachment to the dental surfaces may inform strategies for the maintenance of oral health. Although hydroxyapatite (HA) is a major calcium phosphate component of teeth, effect of biofilm formation on HA surfaces remains poorly characterized. In this study, biofilm-forming abilities by the periodontal pathogens Aggregatibacter actinomycetemcomitans Y4 and Porphyromonas gingivalis 381 were investigated on dense and porous HAs that represent enamel and dentin surfaces, respectively. These experiments showed greater biofilm formation on porous HA, but differing attachment profiles and effects of the two pathogens. Specifically, while the detachment of A. actinomycetemcomitans Y4 biofilm was observed, P. gingivalis 381 biofilm increased with time. Moreover, observations of HA morphology following formation of A. actinomycetemcomitans Y4 biofilm revealed gaps between particles, whereas no significant changes were observed in the presence of P. gingivalis 381. Finally, comparisons of calcium leakage showed only slight differences between bacterial species and HA types and may be masked by bacterial calcium uptake.